2009
DOI: 10.1182/blood-2008-06-162164
|View full text |Cite
|
Sign up to set email alerts
|

A myelopoiesis-associated regulatory intergenic noncoding RNA transcript within the human HOXA cluster

Abstract: We have identified an intergenic transcriptional activity that is located between the human HOXA1 and HOXA2 genes, shows myeloid-specific expression, and is upregulated during granulocytic differentiation. The novel gene, termed HOTAIRM1 (HOX antisense intergenic RNA myeloid 1), is transcribed antisense to the HOXA genes and originates from the same CpG island that embeds the start site of IntroductionHuman HOX gene clusters are known for the prevalence of intergenic transcription between coding genic members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
355
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(362 citation statements)
references
References 57 publications
4
355
1
2
Order By: Relevance
“…Patients with NPM1 mutations exhibit one of the strongest lncRNA signatures, as evidenced by higher lncRNA fold change and lower false discovery rates. It has been reported that NPM1-mutated CN-AML exhibits unique and strong mRNA and miRNA expression profiles characterized by HOX gene and miR-10 family overexpression and CD34 negativity (11,47). Because ∼40% of lncRNAs intersect protein-coding loci and exhibit a strong pattern of coexpression (26), we found many up-regulated lncRNAs overlapping antisense transcripts of HOX genes (e.g., HOXB-AS3) in the NPM1-mutated lncRNA signature.…”
Section: Discussionmentioning
confidence: 75%
“…Patients with NPM1 mutations exhibit one of the strongest lncRNA signatures, as evidenced by higher lncRNA fold change and lower false discovery rates. It has been reported that NPM1-mutated CN-AML exhibits unique and strong mRNA and miRNA expression profiles characterized by HOX gene and miR-10 family overexpression and CD34 negativity (11,47). Because ∼40% of lncRNAs intersect protein-coding loci and exhibit a strong pattern of coexpression (26), we found many up-regulated lncRNAs overlapping antisense transcripts of HOX genes (e.g., HOXB-AS3) in the NPM1-mutated lncRNA signature.…”
Section: Discussionmentioning
confidence: 75%
“…While little evidence exists on lncRNAs functions, their specific expression pattern, promoter conservation, alternative splicing, and association with particular chromatin signatures all suggest that most of these transcripts are functional [11][12][13][14]. Moreover, it is recently claimed that lncRNAs display an enhancer-like function in human cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…HOTAIRM1 expression level was higher in PDAC samples than the mean level in paired non-tumor tissues. HOTAIRM1 is a long intergenic non-coding RNA located at the 3'-end of the HOXA cluster, upregulated during myeloid maturation (71). HOTAIRM1 may affect cell fate by regulating cell cycle progression and serving as a link in the coordinated regulation of an extensive gene expression program.…”
Section: Discussionmentioning
confidence: 99%